Aktualisasi Budaya Inovasi pada Organisasi Sektor Publik - Lathifah, Hilma; Frinaldi, Aldri (YASIN, 2024)
A culture of innovation is not just an option, but an urgent need to maintain the competitiveness of public sector organizations amidst rapid change. In this context, a culture of innovation is a vital aspect in strengthening the competitiveness of an organization, especially in the public sector which plays a crucial role in public services. In researching the actualization of innovation culture in public sector organizations, a qualitative approach with descriptive methods is the right choice. A qualitative approach allows researchers to gain a deep understanding of a complex and multidimensional phenomenon such as innovation culture. From the discussion that has been described, it can be concluded that the actualization of a culture of innovation in public sector organizations is an urgent need in facing the complexity and dynamics of an ever-changing environment. The main problems faced by public sector organizations, such as resistance to change, complex bureaucracy, and low employee involvement, are the main obstacles in realizing an effective innovation culture. However, by adopting a qualitative approach with descriptive methods in research, as well as involving various stakeholders in the process, organizations can gain a deeper understanding of the dynamics of existing innovation culture and explore strategies that can be implemented to overcome them.